The U.S.-Canada security relationship : the politics, strategy, and technology of defense - Haglund, David G.; Sokolsky, Joel J., 1953- (Studies in global security., 2019)
This book focuses on the critical issues shaping the bilateral defense relationship of the U.S. and Canada, including the future of ballistic missile defense, the increased deployment of air- and sea-launched cruise missiles, and the growing debate within Canada over security relations with the US.